BRIDGING CULTURE AND LANGUAGE: INDONESIAN PRESERVICE TEACHERS' PERSPECTIVES ON INTEGRATING LOCAL WISDOM IN ENGLISH LANGUAGE COURSES - Jaya, Hariswan Putera; Sofendi, Sofendi; Mirizon, Soni (University of Kuningan, 2024)
Abstract: This study investigated students’ perceptions of integrating local wisdom into English language skills courses, focusing on its impact on engagement, understanding, and learning experience. The research employed a survey design, collecting data through closed-ended questionnaire with insights from open-ended responses. The participants were pre-service teachers, students enrolled in the English Education Study Program. Descriptive statistics, including means, standard deviations, and frequencies, were used to summarize the responses for each section of the questionnaire in the data analysis. The questionnaire results revealed that students felt more motivated and reported a deeper comprehension of the cultural and social nuances within language use when local wisdom was incorporated into the curriculum.. Qualitative responses highlighted the significance of three main areas: relevant course materials, instructional expertise, and diverse pedagogical approaches. The study recommends ongoing curriculum adaptation to ensure a meaningful, effective blend of language and local cultural knowledge